Ultrafast Photo‐ion Probing of the Ring‐Opening Process in Trans‐Stilbene Oxide. Issue 44 (17th June 2021) - Robinson, Matthew S.; Niebuhr, Mario; Lever, Fabiano; Mayer, Dennis; Metje, Jan; Gühr, Markus
Abstract: The ultrafast photo‐induced ring opening of the oxirane derivative trans ‐stilbene oxide has been studied through the use of ultrafast UV/UV pump‐probe spectroscopy by using photo‐ion detection. Single‐ and multiphoton probe paths and final states were identified through comparisons between UV power studies and synchrotron‐based vacuum ultraviolet (VUV) single‐photon ionization studies. Three major time‐dependent features of the parent ion (sub‐450 fs decay, (1.5±0.2) ps, and >100 ps) were observed. These decays are discussed in conjunction with the primary ring‐opening mechanism of stilbene oxide, which occurs through C−C dissociation in the oxirane ring. The appearance of fragments relating to the masses of dehydrogenated diphenylmethane (167 amu) and dehydrogenated methylbenzene (90 amu) were also investigated. The appearance of the 167 amu fragment could suggest an alternative ultrafast ring‐opening pathway via the dissociation of one of the C−O bonds within the oxirane ring. Abstract : The first sub‐picosecond studies of the excited‐state ring‐opening dynamics of stilbene oxide are presented. Three major decays for the parent ion (sub‐450 fs, (1.5±0.2) ps, and >100 ps), which relate to ring opening at the C−C bond of the oxirane center, were observed. Additionally two fragment ions appeared that might highlight an alternative mechanism that occurs through the dissociation of one of the C−O bonds of the oxirane center.